European Identity and Redistributive Preferences - Joan Costa-i-Font; Frank Cowell (London School of Economics and Political Science (LSE), European Institute, 2015)
How important is spatial identity in shifting preferences for redistribution? This paper takes advantage of within-country variability in the adoption of a single currency as an instrument to examine the impact of the rescaling of spatial identity in Europe. We draw upon data from the last three decades of waves of the European Values Survey and we examine the impact of joining the single currency on preferences for redistribution. Our instrumentation strategy relies on using the exogenous effect of joining a common currency, alongside a battery of robustness checks and alternative instruments. Our findings suggest that joining the euro has a boosting effect on European identity; an opposite and comparable effect is found for national pride. We find that European identity increases preferences for redistribution, and that national pride exerts an equivalent reduction in preferences for redistribution.
Keywords: D69; O52; H53; 330; spatial identity; Europe; welfare state support